Determinants of the effective use of UGC (User-Generated Content) on hotel room bookings by portuguese travellers - Bernardino, Susana (2020)
The presence of user generated content (UGC) on online platforms of hotel room booking operators is changing the way consumers book a hotel room. After a critical evaluation of the technology acceptance models (TAM), the authors discuss the variables that will be employed to predict the effective use of online hotel room bookings by Portuguese travellers. The empirical investigation consists of a linear regression model that was built in order to analyse the data obtained from an online survey of 624 customers of the website Booking.com. The results showed that attitude towards UGC and the perceived ease to use of UGC are important determinants on the buyer’s decision-making process of booking a hotel room. This result shows the relevance of UGC (ratings and reviews) for online booking operators, as UGC could influence the booking of a particular hotel room. Further, the result also brings important implications for hotel managers that pay less attention to the feedback of the customers.